A multi-level comparative analysis of human femoral cortical bone quality in healthy cadavers and surgical safe margin of osteosarcoma patients. (February 2017) - Zhang, Xuelei; Tang, Zhurong; Zhou, Yong; Chen, Xuening; Zhu, Xiangdong; Fan, Yujiang; Zhang, Yu; Yang, Xiao; Tu, Chong-qi; Zhang, Xingdong
Abstract: Osteosarcoma is the most common primary malignancy of bone. However, the potential variation it brings to the adjacent undamaged bone tissue is seldom investigated. In this study, we conducted a multi-level comparison of human femoral cortical bone quality in healthy cadavers (aged 42±11 years) and in resected safe margin of osteosarcoma patients (aged 49±15 years). The objective of this study was to document the changes with exposure to osteosarcoma condition in bone mechanical strength, structural morphology and elementary composition, evaluated by static and dynamic mechanical analysis (DMA), scanning electron microscopy (SEM) imaging, X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR). The resected clinical samples from healthy and osteosarcoma conditioned bones were grouped into the Tumor and Healthy groups, and shaped into regular beam specimens or pulverized according to testing protocols. The results of mechanical tests confirmed osteolytic deteriorations in mineral phase of the Tumor group, in terms of significant reductions in storage modulus (−53.6%, at 1 Hz), bending strength (−53.0%) and stiffness (−64.8%) as compared to the Healthy group. However, the energy dissipation/absorption ability of the collagen phase in the Tumor group did not differ from the Healthy group statistically. Although specimens showed no visible morphological difference, a decline in osteocyte lacunar density in bone specimens from the Tumor group was discovered (−54.4%, p <0.001). Higher magnification observation showed that the cell-free lacunae in the Tumor group were occluded by randomized overgrown collagen fibers. XRD and FTIR analysis further demonstrated a lower hydroxyapatite crystallinity and decreased mineral:matrix ratio in pulverized samples from the Tumor group, mainly due to the prominent Amide peaks. Taken together, these data revealed a previously unrecognized effect of osteosarcoma on the adjacent "normal" bone quality. The current study may provide insights on bone tumor pathology and an advanced understanding of surgical safe margin.